Pengaruh Pelatihan terhadap Kinerja Pegawai Pada Kantor Pertanahan Kabupaten Kerinci - Reni Devita; Muhammad Emil (Universitas Batanghari, 2022)
Human resource management is a part of management or in other words it can be said that human resource management is a field of management that specifically studies human relationships and roles in organizations. Human resource management focuses its discussion on regulating the role of humans in realizing optimal goals. It is clear that human resource management regulates human labor in such a way that organizational goals are realized. Training must be job-specific. Related training by increasing the knowledge, skills and abilities to perform certain job. The term training is used to refer to any process skills or abilities and abilities of employees, so that they are more well adapted to the work environment they are involved in. Training is a process of teaching certain knowledge and skills and attitudes so that employees are increasingly skilled and able to carry out their responsibilities with the better, according to the standard .Performance is how an employee carry out his work or for his work. The Kerinci District Land Office has the task of assisting The Regent carries out government affairs and co-administration tasks in the land and spatial planning sector, and part of the privileges assigned to the land and spatial planning sector. The Kerinci Regency Land Office was first established in 1990, located at JL. Prof. Dr. Sri Sudewi Maschun Sofwan,SH, Koto Renah Village, but in 2019 the Kerinci District Land Office created a new office in the Sebukar Village area, Silihat Laut District The results of the estimation of the effect of training (X) on performance (Y) using the Software Statistical Product and Service Solution (SPSS) 20, the regression equation is obtained as follows: Y = 0.286 + 0.560X In other words, the regression equation above can be said that the regression coefficient of the training variable has a positive influence on employee performance at the Kerinci District Land Office. There is a significant effect of training on employee performance at the Kerinci Regency Land Office, as evidenced by the t count of 43,587> t table of 3,180. From the estimation results 0.631 or 63.1 percent of training (X) is able to explain the Y variable (performance) by 63.1%. Meanwhile 36.9% was explained by other variables not included in the model. Not only education and training affect performance, but there are other variables of 36.9 percent that affect performance.